Implementasi Ina Niang Tana Wawa no Ama Lero Wulan Reta Sebagai Wujud Tertinggi dalam Pewartaan Injil di Sikka, Flores - Ton, Sekundus Septo Pigang; Baju, Viktorius (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2024)
Humans are cultured beings. As a cultured being, his life is definitely inseparable from the culture that has permeated his personality and has been applied in daily life. However, as a cultured being, he needs to also live the gospel as good news that is proclaimed, as well as a different culture. In this case, a study is needed to implement culture in the proclamation of the Gospel. The focus of this article is the Implementation of Ina niang tana wawa no Ama lero wulan reta as the Highest Form, in Evangelization in Sikka, Flores. The writing of this article aims to describe how the implementation of the concept in the proclamation of the Gospel, while strengthening and affirming the faith of the people in Sikka. The findings of this article are first, Ina niang tana wawa no Ama lero wulan reta as the entrance for evangelization. Second, Ama Pu Ama, “Ama Pu Me La'i, Ama Pu Spiritu Santo as a sacramental principle, implies that the whole reality of the universe is sacramental or symbolic which shows a sign of God's majesty (Ama Pu). The method used in this writing is a phenomenological approach, also written in qualitative-descriptive form with the method is a literature study.